Pengaruh Kepercayaan, Kemudahan, dan Promosi terhadap Keputusan Pembelian Secara Online di Lazada.Co.Id - Amirudin M Amin; Hendra Hendra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
With the existence of online shopping sites make it easier for people to transact electronically without being limited by space and time. This research aims to determine the effect of trust, easy, and promotion on purchasing decisions online at lazada.co.id. This research using questionnaire distribution techniques and are is associative which aim to know the causality relationship between the independent variables and the dependent variable. The amount samples as much as 100 respondents who is college students of Pelita Indonesia universities. The technique which use in determine of the sample is the proportinate stratified sampling method. The data analysis method used is multiple linear regression analysis, t test and F test for testing hypothesis testing. The results of this research indicate that the variables of trust, easy, and promotion which that influence significantly to purchase decision. Keywords: trust, easy, promotion, purchasing decisions.